Defining the Learning Curve of Laparoendoscopic Single-site Heller Myotomy. Issue 8 (August 2013) - Ross, Sharona B.; Luberice, Kenneth; Kurian, Tony J.; Paul, Harold; Rosemurgy, Alexander S.
Initial outcomes suggest laparoendoscopic single-site (LESS) Heller myotomy with anterior fundoplication provides safe, efficacious, and cosmetically superior outcomes relative to conventional laparoscopy. This study was undertaken to define the learning curve of LESS Heller myotomy with anterior fundoplication. One hundred patients underwent LESS Heller myotomy with anterior fundoplication. Symptom frequency and severity were scored using a Likert scale (0 = never/not bothersome to 10 = always/very bothersome). Symptom resolution, additional trocars, and complications were compared among patient quartiles. Median data are presented. Preoperative frequency/severity scores were: dysphagia = 10/8 and regurgitation = 8/7. Additional trocars were placed in 12 patients (10%), of whom all were in the first two quartiles. Esophagotomy/gastrotomy occurred in three patients. Postoperative complications occurred in 9 per cent. No conversions to "open" operations occurred. Length of stay was 1 day. Postoperative frequency/severity scores were: dysphagia = 2/0 and regurgitation = 0/0; scores were less than before myotomy ( P < 0.001). There were no apparent scars, except where additional trocars were placed. LESS Heller myotomy with anterior fundoplication well palliates symptoms of achalasia with no apparent scar. Placement of additional trocars only occurred early in the experience. For surgeons proficient with the conventional laparoscopic approach, the learning curve of LESS Heller myotomy with anterior fundoplication is short and safe, because proficiency is quickly attained.